Probability of He+ Ion at Quantum Number 3 ≤ n ≤ 4 in Momentum Space - Bambang Supriadi; Sisilia Nur Hikmah Anggraeni; Merry Khanza Kusuma Wardhany; Fadia Arisma Iswardani; Nabila Ayu Rosyidah; Dwi Pangesti (Jurnal Penelitian Pendidikan IPA, 2024)
Ions resulting from the ionization of helium atoms are known as helium ions. Atom of Helium The probability distribution of the particle locations and velocities inside a helium atom is referred to as probability. Using theoretical study methods, the goal of this research is to find the probability of an electron's position in a helium atom at the quantum number 3 ≤ n ≤ 4. This type of research is non-experimental research by developing previously existing theories. This type of research is non-experimental research by transforming the radial wave function of hydrogenic atoms in position space into a radial wave function in momentum space using the Fourier transformation, then including a number of Gegenbauer functions and using the probability equation of finding an electron in a Helium ion in momentum space. The results of this research provide information regarding the position and probability of the existence of electrons in the helium atom. The probability value for the Helium ion is obtained using the equation P(p) =   which is used to indicate the probability of finding an electron in a helium atom is directly proportional to the principal quantum number (n) and the value of the electron's momentum. The larger the electron momentum interval, the greater the probability.